Empowering women with digital extension in Uganda: Effects of information and role models - Lecoutere, Els; Spielman, David J.; Van Campenhout, Bjorn (2019)
In many developing countries, agricultural extension services are generally biased towards men, with information targeted mainly to male members of a farming household and in formats that are rarely tailored to women. We conduct a field experiment among maize-farming households in eastern Uganda to test whether video-enabled extension messaging affects outcomes directly related to maize management and production. Specifically, we randomly assign men, women, and couples to view videos about improved maize management practices in which male, female, or both male and female actors are featured. We first investigate whether targeting women with information increases their involvement in productive decision-making processes. We then explore whether the provision of information in videos featuring a woman—challenging the idea that maize cultivation is a predominantly male activity—affects outcomes for women. We find that screening videos containing information on maize management and production to women increase their knowledge about improved maize management practices, their role in agricultural decision-making, the adoption of recommended practices and inputs, the quantity of maize sold to the market, and production-related outcomes on women-managed maize plots. However, we also find that challenging role incongruity by featuring women in videos has limited effects.